Amphibians in Zootaxa: 20 years documenting the global diversity of frogs, salamanders, and caecilians - Rivera-Correa, Mauricio; Baldo, Diego; Candioti, Florencia Vera; Orrico, Victor Goyannes Dill; Blackburn, David C.; Castroviejo-Fisher, Santiago; Chan, Kin Onn; Gambale, Priscilla; Gower, David J.; Quah, Evan S.h.; Rowley, Jodi J. L.; Twomey, Evan; et al. (Zootaxa, 2021)
Zootaxa is a mega-journal that since its inception, 20 years ago, has contributed to the documentation of the planet’s biodiversity. Its role concerning terrestrial vertebrates has been crucial especially for amphibians, which are the most threatened class of vertebrates. As current editors of the Amphibia section, we reviewed the state of knowledge of taxonomic publications on amphibians over the last two decades (from 2001 to 2020). Our review reveals that 2,533 frogs, 259 salamanders, and 55 caecilians have been named in these 20 years, mainly in the tropical regions of South America, Asia, and Africa. More than half (57%) of these species descriptions were published in only 10 journals. At least 827 species of the new amphibians (29% of the total) were described in Zootaxa. This mega-journal has served also as a place of publication for monographs and systematic reviews, in addition to short articles documenting the vocalizations of anurans and the morphology of embryos and larvae. Its efficient evaluation process, the freedom of manuscript length, including full-color figures, and free of cost for the authors, has made Zootaxa a favorite for amphibian researchers. In an era of accelerating rates of biodiversity loss, documenting, describing, naming, and proposing evolutionary scenarios for species is, more than ever, an urgent task.